Tanacetum vulgare essential oil as grain protectant against adults and larvae of four major stored-product insect pests. (December 2021) - Kavallieratos, Nickolas G.; Skourti, Anna; Nika, Erifili P.; Mártonfi, Pavol; Spinozzi, Eleonora; Maggi, Filippo
Abstract: In this study the adulticidal and larvicidal effect of tansy, Tanacetum vulgare L. (Asteraceae) essential oil (EO) was estimated against four noxious stored-product insect species; Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), Tenebrio molitor L. (Coleoptera: Tenebrionidae) and Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae). The EO chemical composition, as determined by GC-MS, was dominated by oxygenated monoterpenes (68.2%), with borneol (13.6%), umbellulone (11.7%), artemisia ketone (9.3%), cis -chrysanthenol (6.9%), camphor (5.9%), and terpinen-4-ol (5.5%) as the major constituents. This profile was quite different from those previously reported from other T. vulgare European accessions which are characterized by high content of the toxic trans -thujone. The T. vulgare EO was applied as wheat protectant at two concentrations of 500 and 1000 ppm. Adult and larval mortality levels were estimated after 4, 8 and 16 h and 1, 2, 3, 4, 5, 6 and 7 days. Tanacetum vulgare EO caused complete mortality (100%) to T. castaneum larvae, but only 25.6% to adults at 1000 ppm 6 and 7 days post-exposure, respectively. The mortality rates of T. confusum larvae and adults were 56.7 and 8.9% on wheat treated with 1000 ppm EO, respectively after 7 days of exposure. The ΕΟ caused moderate mortality to T. molitor adults (52.2%), and low mortality to larvae (8.9%), at 1000 ppm at the end of the experimental period. High mortality of O. surinamensis larvae (93.3%) was noticed at 1000 ppm after 7 days of exposure, while only 13.3% of the exposed adults were dead at the same concentration and exposure interval. Overall, the T. vulgare EO could be considered as a potential wheat protectant for the management of important stored-product insects. However, its efficacy depends on the species and the life stage of the target pest. Highlights: T. vulgare EO was dominated by 68.2% oxygenated monoterpenes. T. vulgare EO caused 100% mortality to T. castaneum larvae at 1000 ppm. 94.4% of T. castaneum larvae died on wheat treated with T. vulgare EO at 500 ppm. 93.3% of O. surinamensis larvae died on wheat treated with 1000 ppm T . vulgare EO.